HIGH-PRESSURE MAFIC GRANULITES IN THE TRANS-NORTH CHINA OROGEN: TECTONIC SIGNIFICANCE AND AGE - Zhang J.; Zhao G.; Sun M.; Wilde S.A.; Li S.; Liu S. (My University, 2006)
High-pressure mafic granulites (including retrograded eclogites) have been reported from the Trans-North China Orogen, a Paleoproterozoic orogenic belt along which two discrete continental blocks, referred to as the Eastern and Western Blocks, were amalgamated to form the North China Craton. Extensive metamorphic investigations and geochronology carried out over the last few years provide important insights into the age and significance of these high-pressure granulites, which are critical in understanding of the timing and tectonic processes involved in the assembly of the North China Craton. Most high-pressure mafic granulites in the Trans-North China Orogen preserve the high-pressure granulite facies assemblage garnet+plagioclase+clinopyroxene+quartz, the medium-pressure granulite facies assemblage garnet+plagioclase+clinopyroxene+orthopyroxene±quartz, the low-pressure granulite facies assemblage orthopyroxene+clinopyroxene+plagioclase±quartz, and the amphibolite facies assemblage hornblende+plagioclase. Minor high-pressure granulites preserve the early eclogite facies mineral assemblage of garnet+quartz+omphacite pseudomorph (clinopyroxene+Na-rich plagioclase), indicating that they are retrograded eclogites. These mineral assemblages and their P-T estimates define a clockwise P-T path involving near-isothermal decompression and cooling following the peak high-pressure metamorphism, which suggests that they formed during continent-continent collision. Field mapping and geochronology indicate that the precursors of these high-pressure granulites were mafic dykes which were emplaced at ~1915 Ma and underwent high-pressure granulite facies metamorphism at ~1.85 Ga. Taken together, the high-pressure granulites in the Trans-North China are considered to have resulted from final collision between the Eastern and Western Blocks to form the North China Craton at ~1.85 Ga, not at ~2.5 Ga as recently proposed by some authors. © 2005 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.
Keywords: HIGH-PRESSURE GRANULITE; NORTH CHINA CRATON; P-T PATHS; PALEOPROTEROZOIC TECTONICS; TRANS-NORTH CHINA OROGEN; Paleoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская